A review of the impacts of pumped hydro energy storage construction on subalpine and alpine biodiversity: lessons for the Snowy Mountains pumped hydro expansion project. Issue 1 (2nd January 2020) - Normyle, Anna; Pittock, Jamie
ABSTRACT: The Australian government's proposal to expand the Snowy Hydro Scheme to include a second pumped hydro energy storage (PHES) system, and support for feasibility studies for PHES in Tasmania, offer an opportunity to incorporate more intermittent renewable energy generation into the National Energy Market. However, the infrastructure construction required for PHES expansion may have negative effects for biodiversity in subalpine and alpine areas. To identify the potential effects of PHES on biodiversity in Kosciuszko National Park (KNP), this systematic literature review assesses: (i) the key environmental disturbances likely to arise from PHES construction; and (ii) the specific impacts of these construction processes on biodiversity in subalpine and alpine environments. We find that the effects of PHES construction-related disturbances are likely to be negative for subalpine and alpine biodiversity, with impacts including the proliferation of exotic flora, habitat loss resulting from vegetation clearing, altered landscape hydrology and reduced water quality. Management recommendations to limit these impacts are provided and further research is recommended to assess: (i) the effects of PHES on fish populations in alpine reservoirs; (ii) the utility of spoil as artificial habitat for endemic fauna; and (iii) the chemical and physical impacts of spoil dumping in alpine reservoirs.